Makna Simbolik Dibalik Kain Lurik Solo - Yogyakarta - Suprayitno Suprayitno; Inda Ariesta (Bina Nusantara University, 2014)
As with another woven in the archipelago, woven Lurik has philosophy values and are also loaded with symbolic meaning. Woven Lurik can not be removed from the people’s belief as well as various religious and customs rituals. The purpose of this study is to redescribe the symbolic meaning of the woven Lurik, with a qualitative method approach through the study of literature and interview stages. Philosophy and symbolic meaning of a piece of Lurik normally reflected in the motifs and colors. Woven Lurik with its various pattern is considered to have sacred values that give good luck, advice, guidance, and hope. All of which is reflected in the style sheet / woven motifs.